Factors affecting first service non-return rate of crossbred bulls in Bangladesh condition - RABIDAS, S K; TALUKDER, A K; BARI, F Y; ALAM, M G S (The Indian Journal of Animal Sciences, 2012)
This study was conducted to identify the factors that affect first service non-return rate (NNR) at 56 days after artificial insemination (AI) in Bangladesh condition. Five crossbred bulls from AI center of Bangladesh Agricultural University were used in this study. A total of 1650 cows were inseminated by 2 inseminators. The overall NRR for 5 bulls was 82.9% (72.9 to 87.5%). The highest NRR (87.5%) was observed in a Red Chittagong bull, which is significantly higher than that of Holstein-Friesian (H-F) × Local (L). Cows which were more than 12.5 years old revealed a significantly lower NRR than younger animals. The non-return rate did not vary significantly between the breeds of cows; however, the highest NNR (91.0%) was found in indigenous zebu cows than crossbred cows (H-F × L and Sahiwal × L) (82.4 to 82.9%). Multiparous cows showed lower NNR in comparison to nulliparous and primiparous cows; but this differences did not vary significantly. The cows showed significantly higher NRR (90.9%) when insemination was given during winter than cows which received insemination in summer (NNR 78.0%). The low environmental temperature (<20°C; OR=2.864) was favorable for higher NNR than hot weather (>25C). It is concluded that, individual bull, older and multiparous cows, summer and hot weather negatively affect first service non-return rate in Bangladesh condition.